Central and Eastern Europe (CEE) and South-Eastern Europe (SEE) stock markets: An In-depth analysis - Ihor HURNYAK; Arkadiusz NIEDZWIECKI; Damian PRONIEWSKI; Marek PRONIEWSKI (Communications of International Proceedings, 2023)
Central-Eastern Europe (CEE) and South-Eastern Europe (SEE) both demonstrate similar trends in the development of stock markets and have simultaneously special distinctive mechanisms. If the CEE markets have moved much closer in the direction of unification with the markets of Western Europe and the USA, then the SEE markets partly possess the determination of "looking into the past". The trading relationship between the stock exchanges of Central and Eastern Europe and Southeastern Europe has not yet been thoroughly analyzed. Analyzing the development of stock markets participants of CEE and SEE, the authors applied a wide range of machine learning methods. The Sharpe ratio approach and conception of utility maximization have been used for optimal portfolio analysis. The optimal portfolios on the stock exchanges of CEE and SEE include shares of new industries. The temporary imbalances in the capital markets of CEE and SEE in a certain way make the entry of companies from both regions into each other's stock markets a mutually beneficial step. A special position is the field of software, for which success in the markets of both regions seems completely guaranteed.
Keywords: stock market; software; Sharpe Ratio; prediction model; SEE; CEE